Teachers’ attitudes towards the prevalence of bullying and the specific characteristics of victims - Manić, Iva; Marković, Marija (Specijalna edukacija i rehabilitacija, 2022)
Introduction. Bullying is a phenomenon that implies an imbalance of power between peers. It refers to situations where there are repeated verbal and physical attacks, social exclusion, and emotional, psychological, and sexual abuse of one student by another/other students, where the victim did not cause such behavior of the bully. Objective. The objective of this research was to determine teachers’ attitudes towards the representation of certain forms of bullying and the specific characteristics of the victims. Methods. The sample consisted of 109 teachers from six primary and secondary schools in Pirot. A five-point Likert-type evaluation scale, designed for the purpose of the research, was used for data collection. Results. The research results show that verbal bullying is the most frequently observed form of bullying among students. Also, based on the teacher’s views, it can be concluded that any student can become a victim of bullying, regardless of their specific characteristics. Conclusion. Verbal bullying was identified as the most pronounced form of bullying, while the specifics of students were not singled out as a risk factor at the individual level. Due to the fact that certain forms of bullying are more difficult to be noticed by adults, as well as the possibility that any student can become a victim of peer violence, the preventive action of the school, family, and other subsystems important for the upbringing and education of children is of great importance in preventing this phenomenon.
Keywords: bullying; forms of bullying; characteristics of victims; school; teacher’s attitudes